WEIGHT LOSS, ENCEPHALOPATHY, URINARY DIFFICULTIES AND NUMB FEET IN A NIGERIAN MAN. Issue 11 (9th October 2013) - McColgan, P; Viegas, S; Gandhi, S; Sheikh, F; Pinney, J; Fontana, M; Rowczenio, D; Shah, S; Jaumuktane, Z; Holton, J; Schott, J; Werring, D; et al.
Abstract : Case Report: A 43 year–old right–handed Nigerian man initially presented with weight loss of 20 kg over a 3–month period in March 2011. Over the following year he became progressively more drowsy and confused and developed urinary and erectile dysfunction. Since May 2012 he has suffered recurrent episodes of transient neurological disturbance characterised by slurred speech with right arm and leg weakness lasting 30 minutes. More recently he has developed hearing difficulties and painless paraesthesia. General examination was unremarkable. He had horizontal gaze evoked nystagmus and a brisk jaw jerk, increased tone in the lower limbs, brisk reflexes in the upper and lower limbs and bilateral heel–shin ataxia. Magnetic resonance imaging (MRI) of brain and spine showed extensive leptomeningeal enhancement without any signal change within the parenchyma. Cerebrospinal fluid (CSF) analysis showed a raised CSF protein of 6.4 g/dl. His nerve conduction studies confirmed both a mild large fibre and severe small fibre neuropathy. Autonomic testing showed asymptomatic autonomic neuropathy. Echocardiogram and cardiac MRI suggested cardiac amyloidosis. Meningeal and brain biopsy confirmed widespread amyloid angiopathy involving dura matter, leptomeninges and neocortical blood vessels. After discussion with all relevant specialists it was agreed that the patient was not a suitable candidate for liver transplantation. During his admission he fluctuated from being drowsy but orientated to being very confused with episodes of agitation, paranoia and hallucinations. No ictal changes were captured on electroencephalography (EEG) but he was nevertheless started on Levetiracetam. Arterial blood gas measurement showed evidence of type 2 respiratory failure and overnight oximetry revealed cyclical episodes of oxygen desaturation. Non–invasive ventilation was poorly tolerated. He also developed acute renal failure secondary to clot retention from haematuria, possibly secondary to widespread amyloid angiopathy, however this was treated and he improved. He remains in this fluctuant state. Discussion: Hereditary leptomeningeal amyloidosis is a rare manifestation of transthyretin (TTR) amyloidosis, characterised by amyloid deposition in the meninges of the brain and spinal cord with occasional ocular involvement. Patients present with a wide variety of neurological problems including epilepsy, sub–arachnoid haemorrhage, hearing or visual loss and headache. We described the first case of the TTR Leu12Pro mutation in 1999. To date it has been only described in a total of 3 patients, all European. Here we describe the first report of the TTR Leu12Pro variant in an African patient.